The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1109/tuffc.2009.1164
|View full text |Cite
|
Sign up to set email alerts
|

Models of ultrasonic wave propagation in epoxy materials

Abstract: This paper is concerned with modeling ultrasonic wave propagation in epoxy materials to better understand NDE procedures and to provide reliable input to more complex models of guided wave propagation in layered structures. Different physical models are considered in the context of how well they simulate the (known) linear relationship between bulk wave attenuation coefficients and frequency. The identified models are then extended to simulate wave propagation in materials with mechanical properties, which var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Alternatively, ultrasound techniques can provide continuous evaluation of the dynamic elasticity modulus of the epoxy resin right after mixing, measuring the velocity of propagation in the sample of generated ultrasonic waves [17,18]. Although these wave-based methods allow overcoming some of the drawbacks of the conventional techniques based on the resonance frequency, the ultrasonic methods partially fail when material homogeneity is lacking (as the case of epoxy resin) and present some limitations due to the signal interpretation ambiguities of the received waves [17,22]. A technique based on the use of FOs embedded through the reinforcing fibres of the FRP laminates was proposed by Antonucci et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, ultrasound techniques can provide continuous evaluation of the dynamic elasticity modulus of the epoxy resin right after mixing, measuring the velocity of propagation in the sample of generated ultrasonic waves [17,18]. Although these wave-based methods allow overcoming some of the drawbacks of the conventional techniques based on the resonance frequency, the ultrasonic methods partially fail when material homogeneity is lacking (as the case of epoxy resin) and present some limitations due to the signal interpretation ambiguities of the received waves [17,22]. A technique based on the use of FOs embedded through the reinforcing fibres of the FRP laminates was proposed by Antonucci et al [19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the speed of bulk waves in the adhesive material, which is dependent primarily on the stiffness of the material, may be used to infer the state of cure of the adhesive [3]. This has motivated studies to monitor curing using ultrasonic techniques [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The attenuation associated to the Kelvin-Voigt model is proportional to the square of the frequency but this model has a tendency to overestimate the attenuation. The models of Maxwell and Zener take into account the relaxation time but also overestimate the attenuation [17,21]. For a wide variety of materials (viscous fluids and viscoelastic tissues), the attenuation can be modeled on a finite bandwidth by a power law [12,14] of the following form:…”
Section: Broadband Behavior Of Attenuation and Phase Velocity Dispersmentioning
confidence: 99%